Website-Based Employee Administration System at Tebing Tinggi City Regional Personnel Agency - Nida Syaida Tamba; Sri Wahyuni; Satria Wira Yudha (Journal of Information Technology, computer science and Electrical Engineering, 2024)
Employee administration is a system that contains related information consisting of elements that are guided towards the target in order to achieve ideal results. For that, the system gets input containing information about employee needs. Often this staffing administration is done manually as written in a book. The problem makes the author interested in creating an employee administration site that is useful for making it easier to provide information related to employees. This administration system runs on localhost using the PHP programming language and MySQL as a database. With this administration system application, it can facilitate and speed up employees in getting information wherever and whenever just by accessing the employee administration system site.